ANALISIS STRAIN HARDENING DENGAN VARIASI MEDIA QUENCHING DALAM MENINGKATKAN MUTU PRODUK PENGRAJIN PANDAI BESI SUNGAI PUAR, KAB. AGAM SUMATERA BARAT - Armila, Armila (Rang Teknik Journal, 2019)
Blacksmith at Sungai Puar Region was decreasing caused by low quality and global marked. China’s product more cheaper n hight quality. Heat Treatment process not worked as metallurgy rules, its still in traditional working. Mechanical properties such, toughness, strength, hardness strength can easily be modified by heat treating for medium carbon steel, were subjected to various forms of heat treatment processes like hardening and tempering. Samples were austenitised at 850-9000C followed by holding times and finally they were quenched in salt water, oil, and fresh water. The specimen with the highest hardness was found in samples quenched in salt water, they are 869,66 VHN in salt water, 605.52 in oil, and 652 VHN in fresh water. Its because salt water have hight density n low viscosity were sample cooled fast, and martensite structure obtained, and hardness increased. Micro Vickers hardness used for samples. Behavior of hight hardness quenched in salt water must be learning more, to measure corrosion rate and toughness.